The Fourth Industrial Revolution and the South African Platinum Mining Industry - Timothy, Tshepo (University of the Witwatersrand, Johannesburg, 2021)
Most mining organisations have warmed up to adopting the latest technologies in recent times, as they have the potential to give them an edge in a highly competitive industry. In South Africa, Platinum Group Metals (PGM) are extensive on the African continent of which South Africa holds about 80% of the world’s reserves. It was estimated that the industry exported approximately USD 4.4 billion worth of platinum during 2015, and the industry is a major contributor to the South African economy (Conradie, 2016). Due to dwindling commodity prices and productivity, coupled with safety concerns, the industry is finding itself in a challenging position to be sustainable. It is against this backdrop that a quantitative research approach using quantitative surveys was used to glean/collect data and determine the gaps as informed by the existing profiles vis a vis the required skills and educational profiles of the people in the mining value chain. Mining officials from Sibanye Stillwater mining company, related mining companies and mining students in their personal capacity within the mining industry value chain in South Africa were engaged as study participants. The findings of the study revealed that stakeholder engagement and organisational readiness are linked. The link between stakeholder engagement, Radio-Frequency Identification (RFID), and artificial intelligence (AI) was highlighted. The research also discovered a link between organisational culture and the skills required, as well as the technology relevant to the fourth industrial revolution
A research report presented in partial fulfillment for the degree of Master of Business Administration to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, Johannesburg 2021
Keywords: Stakeholder Engagement; Skills Requirements; Fourth Industrial Revolution Technologies; Platinum Industry; South Africa; SDG-8: Decent work and economic growth